1979
DOI: 10.1002/tera.1420190114
|View full text |Cite
|
Sign up to set email alerts
|

Prevention by diazepam of adverse effects of maternal restraint stress on postnatal development and learning in the rat

Abstract: Rats on days 12--14 of pregnancy were treated with restraint stress alone (9h daily), restraint stress plus diazepam (1 mg/kg, twice daily), diazepam alone, or left as untreated controls. Postnatal development and behaviour was assessed on a wide-ranging battery of tests. Offspring of mothers subjected to restraint stress alone were significantly retarded on a number of developmental measures including growth, ear-opening, cliff avoidance response, auditory startle response and mid-air righting reflex. When ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1980
1980
2003
2003

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…No effect on litter size, length of gestation, or postnatal development of body weight of the progeny was seen. These results agree well with other studies in which comparable doses of diazepam were used (Barlow et al, 1979;Shore et al, 1983). Reduced litter size was observed only after giving rats the very high dose of 100 mg/kg of diazepam twice a day (Massotti et al, 1980).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…No effect on litter size, length of gestation, or postnatal development of body weight of the progeny was seen. These results agree well with other studies in which comparable doses of diazepam were used (Barlow et al, 1979;Shore et al, 1983). Reduced litter size was observed only after giving rats the very high dose of 100 mg/kg of diazepam twice a day (Massotti et al, 1980).…”
Section: Discussionsupporting
confidence: 92%
“…The only significant effect of prenatal diazepam exposure was the reduced mortality by PD 10. It is relevant that Barlow et al (1979) pointed out that some consequences of severe prenatal maternal stress to the progeny may be prevented by concurrent diazepam therapy to the dam. Daily injections may well involve such a stress.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have demonstrated that exposing animals to stressors during pregnancy is associated with lower birth or foetal weights (Calhoun, 1962;Geber, 1966;Smith et al, 1975;Barlow et al, 1979;Beckhardt & Ward, 1983;Anderson et al, 1985;Pinto & Shetty, 1995). However, the impact of psychological factors in the human offspring has been examined in detail, relatively more recently.…”
Section: Introductionmentioning
confidence: 99%
“…Stress (without exposure to chemical agents) can cause behavioral teratogenicity. A study in which groups of pregnant rats were treated with restraint stress alone, restraint stress plus diazepam, diazepam alone, and no medication yielded interesting results (22). The offspring of mothers subjected to restraint stress alone had significant delays on a number of developmental measures, such as growth and reflexes.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…In an earlier article (5) we critically reviewed data from recent studies related to reproductive outcomes for pregnant women exposed to antidepressant treatment. Four prospective investigations (22)(23)(24)(25) have provided new information about the effects of antidepressant exposure. This information must be incorporated in the outcomes considered in the decision-making model we propose (Figure 1).…”
Section: Fetal Toxicitymentioning
confidence: 99%